A merciful secret - Elliot, Kendra (Elliot, Kendra. Mercy Kilpatrick novels., 2018)
Raised off the grid by survivalists, Mercy Kilpatrick believed in no greater safeguard than the backwoods of Oregon. Unforgiven by her father for abandoning the fold for the FBI, Mercy still holds to her past convictions. They're in her blood. They're her secrets--as guarded as her private survival retreat hidden away in the foothills. In a cabin near her hideaway, Mercy encounters a young girl whose grandmother is dying from multiple knife wounds. Hundreds of miles away, a body is discovered slashed to death in a similar way. The victims--a city judge and an old woman living in the woods--couldn't be more different. With the help of police chief Truman Daly, Mercy must find the killer before the body count rises. Mercy knows that the past has an edge on her. So does her family. How can she keep her secrets now ... when they're the only things that can save her?